TUGAS DAN WEWENANG BADAN PEMBERDAYAAN MASYARAKAT, PEREMPUAN DAN KELUARGA BERENCANA (BPMPKB) DALAM MENINGKATKAN KESEJAHTERAAN NELAYAN DI WILAYAH PESISIR KOTA TEGAL - Retno Saraswati, RIFKI ARDY SULARSO, Amiek Soemarmi, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Community empowerment as crucial in the welfare of the public, especially fishermen in coastal areas Tegal that under present conditions are not able to escape the poverty trap, To that end, the authors elaborate further in legal writing entitled